2017
DOI: 10.1080/13607863.2017.1399345
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and social isolation among young and late middle-age adults: Associations with personal networks and social participation

Abstract: Distinct network characteristics were associated with either loneliness or isolation for each cohort, suggesting network factors are independently associated with each outcome, and may fluctuate over time. Network satisfaction was associated with either loneliness or isolation among both cohorts, suggesting perceptions of social networks may be equally important as objective measures, and remain salient for loneliness and isolation throughout the life course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
76
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 51 publications
15
76
1
1
Order By: Relevance
“…In a large scale study comprising 35,712 UK adults, younger adults were found particularly at risk of experiencing severe loneliness during the pandemic in comparison to the older age group (Bu et al, 2020). This result also lends support to earlier studies, which reported younger people to be signi cantly lonelier than older respondents (Barreto et al, 2020;Child & Lawton, 2019). A few possible explanations are offered here.…”
Section: Discussionsupporting
confidence: 82%
“…In a large scale study comprising 35,712 UK adults, younger adults were found particularly at risk of experiencing severe loneliness during the pandemic in comparison to the older age group (Bu et al, 2020). This result also lends support to earlier studies, which reported younger people to be signi cantly lonelier than older respondents (Barreto et al, 2020;Child & Lawton, 2019). A few possible explanations are offered here.…”
Section: Discussionsupporting
confidence: 82%
“…The results of the current study demonstrated the relationship between loneliness and social capital. Speci cally, older people who lacked social capital concerning social participation, social connection, and reciprocity were more likely to experience loneliness, which was echoed by ndings from previous studies [10,20,25,41]. Similar to our results, Nyqvist et al [10] found that infrequent social connection with neighbours had an increased likelihood of being lonely among older people aged 65-80 years in Western Finland.…”
Section: Discussionsupporting
confidence: 90%
“…The results demonstrated the relationship between loneliness and social capital. Speci cally, older people who had less social participation, social connection, and reciprocity were more likely to experience loneliness, which was echoed by ndings from previous studies [11,27,44,45]. In this study, social capital consisted of six dimensions [33,36].…”
Section: Discussionsupporting
confidence: 50%